Clonal Population of Flucytosine-Resistant Candida tropicalis from Blood Cultures, Paris, France - Desnos-Ollivier, Marie; Bretagne, Stéphane; Bernède, Claire; Robert, Vincent; Raoux, Dorothée; Chachaty, Elisabeth; Forget, Elisabeth; Lacroix, Claire; Dromer, Françoise (Emerging infectious diseases, 2008)
Candida tropicalis is a diploid ascomycetes yeast responsible for 4%-24% of candidemia. Resistance to flucytosine is rarely described for this species but was observed for 45 (35%) of 130 C. tropicalis isolates recovered from blood cultures in the Paris area in a 4-year survey. The aims of this study were to test the hypothesis that the flucytosine-resistant isolates could represent a subgroup and to determine the relationship between epidemiologic and genomic data. Epidemiologic data and gene sequences were analyzed, and molecular typing was performed. Our results suggest that a clone of flucytosine-resistant isolates, associated with malignancies and a lower mortality than that for other C. tropicalis isolates, is widespread in the Paris area. We propose the analysis of 2 polymorphic microsatellite markers coupled with URA3 sequencing to track the clone.